Peningkatan Hasil Belajar Pecahan Desimal Melalui Model Pembelajaran Langsung Berbantuan Media Spinner pada Siswa Kelas V Sekolah Dasar - ni putu nia agustini; Made Sujana Andyana (J-SES : Journal of Science, Education and Studies, 2026)
Poor academic achievement among fifth-grade students at SD Negeri 1 Nawakerti in the topic of decimal fractions served as the impetus for this investigation. The primary objective of this study was to enhance students academic performance in decimal fraction content through the implementation of a direct instruction model supported by spinner media. A Classroom Action Research (CAR) design was employed, encompassing two iterative cycles, each incorporating the stages of planning, action, observation, and reflection. Forty fifth-grade students at SD Negeri 1 Nawakerti were selected as research participants. Data were gathered through achievement tests, observational records, and documentary evidence. Findings demonstrated that the consistent application of the direct instruction model with spinner media support produced a measurable and meaningful improvement in student achievement across both cycles. The direct instruction model supported by spinner media is therefore recommended as a viable and effective alternative for mathematics instruction at the elementary school level.